2010
DOI: 10.1007/s00018-010-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Pyk2 to SHPS-1 signaling complex is required for IGF-I-dependent mitogenic signaling in vascular smooth muscle cells

Abstract: In vascular smooth muscle cells, IGF-I stimulates SHPS-1/SHP2/Src complex formation which is required for IGF-I-stimulated cell proliferation. Using SHP2/Src silencing and a Pyk2/Y402F mutant, we showed that Pyk2 was also recruited to the SHPS-1 complex. Pyk2 recruitment to SHPS-1 is mediated via the interaction of Pyk2 Tyr402 and the Src in response to IGF-I. Following Src/Pyk2 association, Src phosphorylates Pyk2 on Tyr881 providing a binding site for Grb2. Cells expressing Pyk2/Y881F showed decreased Grb2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 63 publications
(124 reference statements)
1
21
0
Order By: Relevance
“…That Tyr-491 was the specific phosphotyrosine that mediated Nox4 recruitment to SHPS-1 was shown by demonstrating that cells expressing a mutant form of Nox4 (Y491F) or a cell-permeable peptide containing a Tyr to Asp substitution at position 491, and the Nox4 flanking sequence prevented Nox4/Grb2 association as well as Nox4 recruitment to SHPS-1. To confirm this result, we utilized cells that expressing a Pyk2 Y881F mutant, because our previous study had shown that Pyk2 mediates Grb2 recruitment to SHPS-1 (19). As predicted, cells expressing this mutant had attenuated Nox4 recruitment.…”
Section: Function Of Shps-1-localized Nox4mentioning
confidence: 62%
See 3 more Smart Citations
“…That Tyr-491 was the specific phosphotyrosine that mediated Nox4 recruitment to SHPS-1 was shown by demonstrating that cells expressing a mutant form of Nox4 (Y491F) or a cell-permeable peptide containing a Tyr to Asp substitution at position 491, and the Nox4 flanking sequence prevented Nox4/Grb2 association as well as Nox4 recruitment to SHPS-1. To confirm this result, we utilized cells that expressing a Pyk2 Y881F mutant, because our previous study had shown that Pyk2 mediates Grb2 recruitment to SHPS-1 (19). As predicted, cells expressing this mutant had attenuated Nox4 recruitment.…”
Section: Function Of Shps-1-localized Nox4mentioning
confidence: 62%
“…4E). To further confirm that Grb2 mediated Nox4 recruitment to SHPS-1, we utilized VSMC expressing a Pyk2 Y881F mutant that we had previously shown eliminated Grb2 recruitment to SHPS-1 (19). IGF-Istimulated Nox4/SHPS-1 association was not detected in the Pyk2 Y881F mutant cells (Fig.…”
Section: Grb2 Mediates Nox4 Recruitment To Shps-1 In Response Tomentioning
confidence: 85%
See 2 more Smart Citations
“…The expression vector of the shRNA template for LacZ was also used as a control. The expression plasmids encoding these shRNAs were prepared as described previously (46).…”
mentioning
confidence: 99%